Pengaruh Return On Asset Dan Non Performing Financing Terhadap Tingkat Likuiditas Pada Bank Umum Syariah Di Indonesia Periode 2017-2020 - Aziz Septiatin (Jurnal Penelitian Dan Pengkajian Ilmiah Sosial Budaya, 2022)
This study aims to examine the Effect of Return on Assets and Non-Performing Financing on Liquidity Levels in Islamic Commercial Banks in Indonesia. The main activity of a banking institution is to collect funds and distribute funds, so that people feel safe entrusting their funds, the banking sector must be able to maintain the level of liquidity because the level of liquidity can be known whether a banking institution is healthy or not, in this study the measurement used is the ratio Financing to Deposit Ratio (FDR). The research method used is a type of quantitative research with a descriptive format. The analytical method used is the classical assumption test method, multiple linear regression test, and hypothesis testing consisting of t test, f test, and coefficient of determination. There are 8 banks as samples in this study. The results showed that based on the t-test the ROA variable had an effect on the level of liquidity, the NPF variable had no effect on the level of liquidity. Meanwhile, based on the f test, the variables of NPF and ROA simultaneously have a significant and significant effect on the liquidity level of Islamic Commercial Banks in Indonesia.